Practices and strategies of informal assessments on grammar rules among second language learners - Jason V. Chavez; Rolly G. Salveleon; Ma. Theresa L. Eustaquio; Haydee G. Adalia; Ma. Pilar T. Rosaldo; Joseph B. Quinto; Salita D. Dimzon; Sar-Ana M. Abdurasul; Rasmil T. Abdurasul; Ivy M. Nazareth (International Journal of Evaluation and Research in Education (IJERE), 2026)
While informal assessment offers authentic insights into second language (L2) grammar acquisition, the specific strategies and implementation challenges remain underexplored. This study investigated the practices employed by L2 educators in conducting informal grammar assessments and the obstacles they encounter. Using a qualitative exploratory design, 20 purposively selected language educators from diverse linguistic regions in the Philippines participated in semi-structured interviews. Data were analyzed using reflexive thematic analysis. The findings revealed a pedagogical shift from static testing to stealth monitoring, characterized by contextualized micro-checks, gamified strategies to lower affective filters, and peer-scaffolded evaluation. However, significant challenges emerged, specifically the tension between assessment validity and reliability, as well as cognitive overload due to the dual burden of instruction and real-time data recording. The study concluded that while educators prioritize the authenticity of low-stakes assessment, effective implementation requires enhanced assessment literacy and structural support to mitigate subjectivity and operational fatigue.